‘Omdat wie de waarheid wil zien, de waarheid moet leeren liefhebben’. De invloed van J.Th. de Visser, Nederlands eerste minister van Onderwijs, Kunsten en Wetenschappen (1918-1925), op het nationale wetenschapsbeleid - Bruinsma, Mette (Studium, 2019)
The Dutch Ministry of Education, Culture and Sciences celebrated its centenary in 2018. Upon its establishment one hundred years ago, the Ministry was intended to be a temporary wing of government, formed solely to arrange the results of the Dutch ‘school struggle’: namely, achieving agreement on the equalization of public financing for religious schools. The fact that the Ministry remains in operation today, with its current size and financial and political responsibilities, demonstrates the active involvement of The Hague in educational policy and provision.In this paper, the role of the first Minister of Education, Arts (later changed to Culture) and Sciences, J.Th. de Visser, is analysed with specific regard to the positioning of science policy in the newly developed Ministry. The principal reason to establish this new Ministry was primary education. However, how did De Visser shape the institutional relationship between politics and sciences in the Netherlands during his two terms of office? The true, the good and the beautiful were De Visser’s key themes, and as the first minister of this not-so-temporary ministry, he played a small but significant role in the national history of science policy formulation.